ANALISIS HUBUNGAN SELF-REGULATED LEARNING TERHADAP KEMAMPUAN BERPIKIR REFLEKTIF MATEMATIS SISWA SMP SYSTEMATIC LITERATURE REVIEW - Anisa Anisa; Heni Pujiastuti; Hepsi Nindiasari (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2026)
Mathematical reflective thinking ability is a higher-order skill vital in mathematics education. Yet, research on its link with self-regulated learning (SRL) among junior high school students is limited and unsystematically reviewed. This study examines the relationship between SRL and mathematical reflective thinking ability through a 10-year (2016–2026) systematic literature review, identifying patterns and implications for mathematics education at the junior high school level. Using Systematic Literature Review (SLR) per PRISMA guidelines, searches on Google Scholar, ERIC, and accredited national journals employed keywords: